Disposability and ordinariness in the New Europe of Damjan Kozole’s Spare Parts - Mendes, Ana Cristina (2019)
This chapter studies the early twenty-first-century representation of disposability, violence, and differentiated citizenships in Damjan Kozole’s cross- border film Spare Parts (2003). The emphasis of the analysis lies on the imaginaries of disenfranchisement involving the migrant characters – who might be refugees, temporary or guest workers, genocide survivors, or economic migrants – ineligible applicants for visas that inhabit Kozole’s cinematic narrative and are transported across borders by Slovenian human traffickers. The issue of illegal border crossings in the context of New Europe is set against the backdrop of Slovenia’s integration into the European Union, which would take place a year after the theatrical release of Spare Parts. Concurrently, the focus is on how ordinariness and familiarity, the anti-heroic and the commonplace, can be interpreted in the thematic of border crossings (or underpassings) and movement (mobility and its opposites – stasis, inertia, and stagnation).